CD98 siRNA-loaded nanoparticles decrease hepatic steatosis in mice. Issue 2 (February 2017) - Canup, Brandon S.B.; Song, Heliang; Le Ngo, Vu; Meng, Xiangxiao; Denning, Timothy L.; Garg, Pallavi; Laroui, Hamed
Abstract: Non-alcoholic fatty liver disease (NAFLD) is characterized by excessive lipid hepatic accumulation. Here, we investigated whether a reduction of CD98 expression mediated by CD98 siRNA-loaded nanoparticles (NPs) could attenuate liver disease markers in a mouse model of NAFLD. NPs were generated using a double emulsion/solvent evaporation technique. Mice fed a high fat diet for 8 weeks to induce fatty liver were treated with vein tail injections of CD98 siRNA-loaded NPs. In vitro, HepG2 treated with CD98 siRNA-loaded NPs showed significant downregulation of CD98 leading to a significant decrease of major pro-inflammatory cytokines and markers. In vivo, CD98 siRNA-loaded NPs strongly decreased all markers of NAFLD, including the blood levels of ALT and lipids accumulation, fibrosis evidence and pro-inflammatory cytokines. In conclusion, our results indicate that CD98 appears to function as a key actor/inducer in NAFLD, and that our NPs approach may offer a new targeted therapeutic for this disease.